Plastination of Specimens by Recycling Environmental Pollutants - Mutturaj, R. P.; Prasad, R. V.; Jamuna, K. V.; Murty, C. V.; Ramkrishna, V. (Indian Journal of Veterinary Anatomy, 2015)
The kidney, brain, heart, liver, limb, head, and genitalia of male and female calves were collected from slaughter house and were plastinated by recycling equal quantity of plastic tea cups and thermocol 15% each. The average shrinkage was 16-48.5% and individually brain, liver, and heart recorded shrinkage percentage of 45, 23, and 16, respectively. The color of plastinated brain and heart and other specimens remained normal except liver which altered slight dark in color. The consistency of all the organs was hard but there was no change in morphological details.